Serum FGF21 Levels Predict the MACE in Patients With Myocardial Infarction After Coronary Artery Bypass Graft Surgery - Xie, Wei; Li, Dan; Shi, Yaru; Yu, Ning; Yan, Yu; Zhang, Yingchao; Yu, Qiongli; Li, Yulin; Du, Jie; Lin, Zhuofeng; Wu, Fan (Frontiers in Cardiovascular Medicine, 2022)
Objectives Prognosis evaluation in myocardial infarction (MI) patients with major adverse clinical events (MACE) undergone coronary artery bypass graft (CABG) is greatly important to identify the high-risk patients. Elevated metabolic hormone fibroblast growth factor 21 (FGF21) is associated with the risk of MI. Our aim of this study is to assess the relationship between FGF21 and the incidence of MACE in patients with MI after CABG surgery. Methods Patients with three-vessel disease who scheduled for first-time isolated CABG were enrolled this project and underwent to evaluate the incidence of MACE during 48 hours after CABG surgery, as well as to collect serum samples for FGF21 levels in both preoperative- and postoperative-CABG (pre-CABG and post-CABG). Results A total of 265 patients with MI undergoing CABG were enroll in this study, 21 patients occurred MACE during 48 hours after CAGB surgery. Serum FGF21 levels of patients with MACE at post-CABG were significantly higher than that in patients without MACE (553.7(433.6) vs. 291.7(334.4), p<0.001). Furthermore, among 81 individuals of these 265 patients, a lower level of FGF21 in preoperative-CABG (pre-CABG) and a higher level of FGF21 at postoperative-CABG (post-CABG) were observed in MI patients with MACE as compared to those without MACE respectively [(275.0(260.4) vs. 410.3(420.7), p=0.049; 550.7(519.9) vs. 370.6(441.2), p=0.031]. In addition, serum FGF21 levels of MI patients with MACE at post-CABG were significantly increased compared with the baseline levels in pre-CABG [550.7(519.9) vs.275.0(260.4) p<0.001]. However, these profiles were not observed in patients without MACE [410.3(420.7) vs. 370.6(441.2), p=0.2137]. Logistic regression analysis demonstrated that both serum FGF21 and CK-MB levels at post-CABG were independently associated with the incidence of MACE in patients with MI after CABG surgery. Finally, ROC analysis for FGF21 levels of 265 MI patients at post-CABG identified 455.4 pg/ml as an optimal cut-off value to predict MACE, with a sensitivity and specificity of 91.7% and 68.4% respectively. Conclusion: Serum FGF21 levels at post-CABG are independently associated with the incidence of MACE in patients with MI undergone CABG. Measurement of FGF21 may help distinguish patients with MI at the high risk of MACE after CABG surgery.